Działalność informacyjna ubezpieczycieli jako element ochrony praw poszukujących ochrony ubezpieczeniowej i klientów zakładów ubezpieczeń - Przybytniowski, Jarosław W. (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The aim of the article was to inform about information activity of the insurance companies, and insurance intermediaries. Their duties in relations with customers were also introduced. In it analysis was used Customers insurance consciousness.The article emphasized the role of the Insured Intercessor Office and also has some information about Amicable Court working along with that Office.It also paid attention into institutions which have a task to protect the rights of the insurance companies customers. (original abstract
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 174-190